Preoperative botulinum neurotoxin A for children with bilateral cerebral palsy undergoing major hip surgery: a randomized double‐blind placebo‐controlled trial. (15th January 2019) - Will, Elspeth; Magill, Nicholas; Arnold, Rebecca; Davies, Megan; Doherty, Gary; Fairhurst, Charlie; Roposch, Andreas; Lundy, Claire; Norman‐Taylor, Fabian
Abstract : Aim: To assess whether preoperative botulinum neurotoxin A (BoNT‐A) affects pain after major hip surgery for children with bilateral cerebral palsy (CP). Method: This was a randomized, parallel arms, placebo‐contolled trial. Children with hypertonic CP aged 2 to 15 years awaiting bony hip surgery at a tertiary hospital were randomized to receive either BoNT‐A or placebo injections into the muscles of the hip on a single occasion immediately before surgery. The primary outcome was the paediatric pain profile (PPP), which was assessed at baseline and weekly for 6 weeks. Treatment allocation was by minimization. Participants, clinicians, and outcome assessors were masked to group assignment. Results: Twenty‐seven participants (17 males, 10 females; mean 8y 8mo [SD 3y 9mo], range 3y 4mo–15y 10mo) were allocated to BoNT‐A and 27 participants (14 males, 13 females; mean 8y 11mo [SD 3y 5mo], range 4y 1mo–15y 2mo) to placebo. Mean (SD) PPP at 6 weeks for the BoNT‐A group ( n =24 followed up) was 10.96 (7.22) and for the placebo group ( n =26) was 10.04 (8.54) ( p =0.69; 95% confidence interval [CI] –4.82, 3.18). There were 16 serious adverse events in total during 6 months of follow‐up ( n =6 in BoNT‐A group). Interpretation: Use of BoNT‐A immediately before bony hip surgery for reducing postoperative pain for children with CP was not supported. What this paper adds: Botulinum neurotoxin A (BoNT‐A) does not reduce postoperative pain following bony hip surgery. BoNT‐A also does not affect postoperative quality of life. What this paper adds: Botulinum neurotoxin A (BoNT‐A) does not reduce postoperative pain following bony hip surgery. BoNT‐A also does not affect postoperative quality of life. This article is commented on by Gormley on page 997 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Resumen: Neurotóxina A botulínica preoperatoria para niños con parálisis cerebral bilateral que van a ser sometidos a una cirugía mayor de cadera: un ensayo aleatorio, doble ciego, controlado con placebo: Objetive: Evaluar si la neurotóxina A botulínica preoperatoria (BoNT‐A) afecta el dolor después de una cirugía mayor de cadera en niños con parálisis cerebral bilateral (PC). Método: Este fue un ensayo aleatorio, con brazos paralelos, controlado con placebo. Los niños con PC hipertónica de 2 a 15 años de edad que esperaban una cirugía de cadera en un hospital terciario se escogieron al azar para recibir inyecciones de BoNT‐A o de placebo en los músculos de la cadera una sola administración previa a la cirugía. El resultado primario fue el perfil de dolor pediátrico (PPP, siglas en ingles), que se evaluó al inicio del estudio y semanalmente durante 6 semanas. La asignación del tratamiento fue por minimización. Tanto los participantes, como los clínicos y evaluadores de resultados, eran desconocidos para la asignación de grupo. Resultados: Veintisiete participantes (17 varones y 10 mujeres; medios 8 años 8 meses) [Desviación Estandar SD 3 años 9 meses], rango 3 años 4 meses‐15 años 10 meses) se les administro BoNT‐A y 27 participantes (14 varones y 13 mujeres; media 8 años 11 meses [SD 3 años 5 meses], rango 4 años 1 mes – 15 años 2 meses) a placebo. La PPP media (SD) a las 6 semanas para el grupo de BoNT‐A (n = 24 seguidas) fue de 10, 96 (7, 22) y para el grupo de placebo (n = 26) fue de 10, 04 (8, 54) (p = 0, 69; intervalo de confianza del 95% [CI, siglas en ingles] –4, 82, 3, 18). Hubo 16 eventos adversos graves en total durante 6 meses de seguimiento (n = 6 en el grupo BoNT‐A). Interpretación: El uso de BoNT‐A inmediatamente antes de la cirugía de cadera con el fin de reducir el dolor postoperatorio en niños con PC no fue consistente. Abstract : Neurotoxina botulínica A pré‐operatória para crianças com paralisia cerebral bilateral submetidas a grande cirurgia de quadril: um estudo randomizado, duplo‐cego, controlado por placebo: Objetivo: Avaliar se a neurotoxina botulínica tipo A (BTA) pré‐operatória A afeta a dor após grande cirurgia de quadril em crianças com paralisia cerebral bilateral (PC). Método: Este foi um estudo randomizado, com braços paralelos e controlado por placebo. Crianças com PC espástica com idade entre 2 a 15 anos aguardando cirurgia óssea de quadril em um hospital terciário foram randomizadas para receber ou BTA ou injeções de placebo nos músculos do quadril em uma única ocasião imediatamente antes da cirurgia. O desfecho primário foi o perfil de dor pediátrica (PDP), que foi avaliado na linha de base e semanalmente por 6 semanas. A alocação de tratamento foi por minimização. Os participantes, clínicos e avaliadores de resultados foram cegados quanto a atribuição de grupo. Resultados: Vinte e sete participantes (17 homens, 10 mulheres; média de 8 anos e 8 meses [DP 3 anos e 9 meses], com idade entre 3 anos e 4 meses à 15 anos e 10 meses) foram alocados para o grupo BTA e 27 participantes (14 homens, 13 mulheres; média de 8 anos e 11 meses [DP 3 anos e 5 meses], com idade entre 4anos e 1mês à 15anos e 2 meses) foram alocados no grupo placebo. A média (DP) do PDP às 6 semanas para o grupo BTA ( n = 24 ) foi de 10, 96 (7, 22) e para o grupo placebo ( n = 26 ) foi de 10, 04 (8, 54) ( p = 0, 69; intervalo de confiança de 95% [IC] ‐4, 82, 3, 18). Houve 16 eventos adversos sérios no total durante 6 meses de acompanhamento ( n = 6 no grupo BTA). Interpretação: O uso da BTA imediatamente antes da cirurgia óssea do quadril para reduzir a dor pós‐operatória em crianças com PC não foi apoiado.